Revisiting the history of the Ostrusha Tomb: new data from pottery deposits - Chavdar Tzochev (Българско е-Списание за Археология)
The Ostrusha tomb is remarkable for its monolithic chamber with hybrid Achaemenid-Greek architecture and a painted ceiling. It was planned and built as a free-standing tomb but was later incorporated into a larger structure. The history of its construction and use remains unsettled, as valuable information was lost in hasty excavation. This paper presents the first comprehensive study of the pottery collected during the excavation and attempts to reconstruct its archaeological context based on surviving descriptions and photographs. Contrary to previous suggestions, the ceramic material does not come from the interior of the tomb or from a ritual pyre. It was originally deposited at different locations in the area of the mound. The relationship of these deposits to the tomb, if any, cannot be reconstructed. The fragmented vessels do not provide firm chronological limits for the different building phases of the monument. However, the majority of the pottery belongs to the third quarter of the 4th c. BC, and it is very likely that these vessels were deposited in connection to a burial. This suggests that the initial structure of the tomb, the monolithic chamber, was completed by ca 325 BC. The activity in the area of the tomb continued until soon after ca 300 BC. The extension of the tomb, with its additional chambers, appears to have been abandoned and buried under the mound before it was completed.